Study on Health Content on TikTok: Eating Habits and Smoking Cessation Programs - AlSaeed, Najwa; Gorpe, Tevhide Serra (Journal of Posthumanism, 2024)
The study addresses TikTok health content, with a focus on eating habits and smoking cessation programs. The target age group ranges between 13 and 24 years in the Kingdom of Saudi Arabia. The study covers the period from June to December 2024. In addition, the study aims to analyze TikTok videos with a focus on narrative patterns, visual strategies, and the role of artificial intelligence (AI) in designing and disseminating messages. The content analysis method was adopted for the research. Data is represented by (67) videos that were collected from the TikTok application by searching keywords. For example, keywords used were inclusive of “eating habits”, “dieting”, “healthy food alternatives”, “Saudi anti-smoking campaigns”, and “dangers of smoking” among other keywords. The findings have revealed that, as far as health-oriented content is concerned, the usage of informational videos amounts 70.1% of the all forms of contents amongst Saudi users in general and adolescents in particular; which is a percentage that indicates that TikTok could be used as an effective platforms for disseminating health-related content among Saudi adolescents and youth. It is worth mentioning that videos on smoking cessation might become a strong tool for influencing youth's health behavior if enriched with more innovative techniques and approaches, placing the active engagement of the audience in the foreground. Future research should seek to examine how interactive features, influencer collaboration, and AI-driven content personalization can further optimize engagement and behavior change. These could refine the content strategies so that TikTok becomes an even more effective medium to encourage healthier lifestyles and reduce harmful habits among young audiences in Saudi Arabia.